CORRUPTION AND THE FORMATION OF CHARACTER IN INDONESIA'S YOUNG GENERATION: AN EMPIRICAL STUDY OF SOCIAL VALUES - An’umillah, Azifah; Lutfiah, Nayla; Sofwatunnisa, Najwa Aulia; Wahyuningsih, Yona (Yayasan Amanah Nur Aman, 2025)
The phenomenon of corruption in Indonesia has become a complex and systemic social problem , transcending moral, legal, and cultural boundaries. Corrupt practices not only cause material losses and undermine the governance system, but also have a significant impact on the character formation of the younger generation. This study aims to analyze the relationship between corrupt practices and the formation of moral values, ethics, and integrity of Indonesia's younger generation through a mixed literature study approach. This method combines systematic review ( Systematic Literature Review (SLR) with theoretical analysis of morality and social issues. The study results show that corruption causes a degradation of the values of honesty, responsibility, and social trust among adolescents and young adults. The crisis of public role models reinforces moral dissonance, which hinders the development of post-conventional character. The main findings confirm that anti-corruption character education based on the social ecosystem—including family, school, media, and community—plays a crucial role in building the moral immunity of the younger generation. This study suggests a Social -Moral Immunity model. Framework (SMIF) which emphasizes collaboration between the government, educational institutions, and civil society to form a generation with integrity and resilience against the normalization of corrupt behavior.